Facilitations in Paying Social Security Contributions – Terminological Issues - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu, 2014)
The provides an analysis of the term “reductions” in reference to paying contributions. It has been indicated that social insurance debt write offs are not recognized as reductions. Moreover, the author proposes a modification of the term “the mechanisms used to facilitate the payment of the contribution by the payers” and an expansion of its scope of meaning.